2018
DOI: 10.1007/s13193-018-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Fracture of Subclavian Venous Chemoport Device at Costoclavicular Junction: Pinch-off Syndrome

Abstract: Chemoport is most commonly used venous access devices for instillation of chemotherapeutic drugs in cancer care. Mechanical complications like catheter fracture can lead to serious morbidity, albeit occurring rarely. We present a case of a 35-year-old lady, a case of carcinoma breast, who had spontaneous fracture of chemoport access device in subclavian vein at the level of clavicle after four successful cycles of chemotherapy. The fracture was suspected on chest x-ray and was subsequently confirmed on contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There is also much controversy about the association between the TICVAP venous insertion site and a retained catheter. Numerous studies have reported that LSCV catheterization is associated with more complications, such as catheter fracture, pinch off syndrome, thrombosis, or stuck catheter [ 11 – 14 ]. In our study, the TICVAP venous insertion site of all patients in Group S was LSCV.…”
Section: Discussionmentioning
confidence: 99%
“…There is also much controversy about the association between the TICVAP venous insertion site and a retained catheter. Numerous studies have reported that LSCV catheterization is associated with more complications, such as catheter fracture, pinch off syndrome, thrombosis, or stuck catheter [ 11 – 14 ]. In our study, the TICVAP venous insertion site of all patients in Group S was LSCV.…”
Section: Discussionmentioning
confidence: 99%